Agency of the Self and the Uncertain Nature of the Beloved in Persian Love Mysticism: Earthly, Ethereal, Masculine, or Feminine? - Mahdieh Vali-Zadeh (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2022)
It seems that the controversies over the nature of the beloved in classical Persian mystic poetry (also known as Sufi poetry) as an earthly or ethereal phenomenon would never end. Those in favor of the celestial reading of it consider their counterparts to be narrow-minded. The adherents of terrestrial love, though, see mystical readings dogmatic and outdated, prevailed by traditionalists. The topic gets even more complicated when one takes into account the attitudes in the medieval Muslim world toward pederasty, shāhid-bāzī, on the one hand, and the Divine Feminine /Masculine Beloved, on the other hand, and, thus, the gender of this beloved. The present article explores the beloved in Persian classical mystical poetry via five different but related approaches: historical, philosophical, translational and comparative, linguistic and poetic, and, ultimately, developmental. The study concludes that an essentialist reading of the beloved in Persian love mystic poetry would create numerous problems, and that the spirit of Persian classical poetry in this regard is the spirit of uncertainty with a certain purpose: it is the manifestation of the self-poet’s agency, choosing one’s object of desire without explicitly revealing it and, thus, living one’s own life of choice without fearing the threads of religious fundamentalism.